Scaphoid Cysts: Literature Review of Etiology, Treatment, and Prognosis. (November 2019) - Safran, Tyler; Hazan, Jessica; Al-Halabi, Becher; Al-Naeem, Hassan; Cugno, Sabrina
Background: Cystic lesions of the carpal bones are rare entities that are infrequently reported in the literature. Scaphoid intraosseous cystic lesions represent a rare subset of carpal bone cysts. This review aims to summarize the available evidence on the evaluation and treatment of scaphoid cystic lesions to help guide clinical management.Methods: Systematic electronic searches were performed using PubMed, Ovid, and Embase databases. Studies included were graded for their risk of bias. Pooled descriptive statistics were performed on incidence, etiology, physical exam findings, treatment, and follow-up.Results: A total of 38 patients representing 41 scaphoid cystic lesions were pooled from 27 articles. Patients presented with wrist pain without fracture (n = 27), pathological fracture (n = 9), swelling only (n = 1), or were asymptomatic (n = 4). Cystic lesions of the scaphoid were initially revealed on imaging with radiographs alone (n = 22), radiographs in combination with computed tomography (CT) (n = 10) or magnetic resonance imaging (n = 6), CT alone (n = 1), or using all 3 modalities (n = 2). Intraosseous ganglia were identified most frequently (n = 31), followed by "bone cyst-like pathological change" (n = 3), unicameral bone cysts (n = 2), aneurysmal bone cysts (n = 2), primary hydatid cysts (n = 2), and cystic like changes post fall (n = 1). Treatment modalities included curettage and bone graft (n = 39) or below-elbow cast (n = 2). On follow-up (average of 21.3 months; n = 40), all patients improved clinically after treatment and were found to have full wrist range of motion without pain (n = 31), slightly reduced grip strength (n = 3), limited range of motion (n = 2), or persistent mild discomfort (n = 2).Conclusions: Scaphoid cystic lesions are most commonly intraosseous ganglia, but can include other etiologies as well. The main presenting symptom is radial wrist pain that usually resolves after treatment. The presence of intracarpal cystic lesions should be considered in the differential diagnosis of wrist pain.